Practical Techniques in Flap Surgery - Hirase, Yuichi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
This book was written for orthopedic and plastic surgeons who wish to learn about reconstructive surgery of the extremities and trunk. For reconstructions of the extremities and trunk, surgeons need information on both orthopedic and plastic surgery. However, orthopedic surgeons are generally not familiar with the reconstruction of soft tissue, and plastic surgeons have little experience with osseo-tendinous system reconstructions. For those reasons, there is a definite need for a book detailing both fields of surgery. Because many existing books focus on only the type of flap, it is difficult for doctors to distinguish which flap is best for their patients in need of reconstructive surgery. In this book, chapters are based not on the flap but the injury site. In the each chapter, pitfalls and candidate flaps are described for the reconstruction of each site. Additionally, the operative steps are explained with the help of numerous high-quality photos, offering a unique valuable resource for orthopedic and plastic surgeons faced with these challenges. .
Chapter 1 : Reconstruction of Upper Arm and Medial and Lateral Elbow -- Chapter 2 : Reconstruction of Forearm Region -- Chapter 3 : Reconstruction of Dorsum of Hand -- Chapter 4 : Degloving Injury -- Chapter 5 : Reconstruction of Palm and Wrist Area -- Chapter 6 : Reconstruction of First web space Area -- Chapter 7 : Reconstruction of Finger Trunk -- Chapter 8 : Reconstruction of Fingertip -- Chapter 9 : Toe Transfer -- Chapter 10 : Nail Reconstruction -- Chapter 11 : Reconstruction of Mediastinitis/ Pyothorax/ Abdominal Incisional Hernia -- Chapter 12 : Reconstruction of Inguinal Region -- Chapter 13 : Reconstruction of the Gluteal, Sacral, and Trochanteric Regions -- Chapter 14 : Patella Region Reconstruction -- Chapter 15 : Anterior lower leg reconstruction -- Chapter 16 : Reconstruction of Distal 1/3 of Lower Leg -- Chapter 17 : Reconstruction of Achilles Tendon Area -- Chapter 18 : Reconstruction of Calcaneal Region/ Lateral Plantar Region -- Chapter 19 : Reconstruction of the Plantar Forefoot -- Chapter 20 : Reconstruction of Dorsum and Amputated Foot Stump -- Chapter 21 : Reconstruction of Dorsum of Toes -- Chapter 22 : Nerve Transplant & Nerve Transfer -- Chapter 23 : Transplantation of Bone and Joints -- Chapter 24 : Fat graft -- Chapter 25 : Muscle graft.
Keywords: Medicine; Orthopedics; Plastic surgery; Medicine & Public Health; Plastic surgery; Surgical Orthopedics